Thoracodorsal artery perforator fasciocutaneous flap: A versatile alternative for coverage of various soft tissue defects - Sever, Celalettin; Uygur, Fatih; Kulahci, Yalcin; Karagoz, Huseyin; Sahin, Cihan (Indian Journal of Plastic Surgery, 2012)
Objective: The thoracodorsal artery perforator (TDAP) flap has contributed to the efficient reconstruction of tissue defects that require a large amount of cutaneous tissue. The optimal reconstruction method should provide thin, and well-vascularized tissue with minimal donor-site morbidity. The indications for the use of this particular flap with other flaps are discussed in this article. Materials and Methods: Thirteen patients underwent soft tissue reconstruction using TDAP flaps between 2009 and 2011. Of those, there were four cases of antecubital burn contracture, three cases of axillary burn contracture, two cases of giant hair cell nevus of upper extremity, two cases of axillary reconstruction following severe recurrent hidradenitis, and two cases of crush injury. All patients were male and their ages ranged from 20 to 23 (average, 21 years). The mean follow-up period was 8 months (range, 4-22 months). Results: All reconstructive procedures were completed without any major complications. Minor complications related to transfered flaps were wound dehiscence in one case, transient venous congestion in two cases. Minor complication related to the donor site was seroma in one case. The success rate was 100%, with satisfactory cosmetic results. Conclusions: The TDAP flap is a safe and extremely versatile flap that offers significant advantages in acute and delayed reconstruction. Although the vascular anatomy may be variable, free and pedicled TDAP flap is a versatile alternative for soft tissue defects. It adapts very well to the soft tissue defects with acceptable donor site scar.
Keywords: Burn contracture; hidradenitis suppurativa; soft tissue defects; the thoracodorsal artery perforator; thoracodorsal artery perforator flap